In situ localization of heat-shock proteins and cell death labelling in the salivary gland of acaricide-treated honeybee larvae - Silva-Zacarin, Elaine C. M.; Gregorc, Ales; Silva de Moraes, Regina L. M. (Edp Sciences S A, 2006)
The effects of the acaricides, rotenone and oxalic acid (OA) on salivary glands of honeybee larvae were evaluated. Immunohistochemical methods were used to detect cell death and heat-shock protein (HSP70 and 90) localizations. Heat-shock proteins (HSP70 and 90) were localized in the cytoplasm and/or the nuclei of secretory gland cells, both under stress and in normal conditions. In rotenone-treated larvae, there were no changes in the normal level of cell death and also there were no morphological alterations in the secretory cells. In the larvae treated with oxalic acid, the salivary gland showed varying degrees of morphological cellular alteration and an increase in the cell death level. The present data suggest that stress-induced HSP70 might have an antiapoptotic effect while the stress-induced HSP90 might have a chaperone function in the larval salivary glands.
Keywords: Apis mellifera; silk gland; cellular stress; immunohistochemistry; rotenone; oxalic acid